Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." -- Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

En finir avec la "condition" féminine? - Fraisse, Geneviève (Féminin masculin : mythes et idéologie, 2006)
Keywords: approches et analyses; cours; discipline; europe; fem1000; france; philosophie; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions

Anti-Essentialism and Intersectionality - Grillo, Tina (Theorizing feminisms a reader, 2006)
'What is oppression ?' 'What should be done about it ?' Organized around these questions, Theorizing feminisms : a reader provides an overview of theoritical feminist writing about the quest for gender justice. Incorporating both classic and cutting-edge material, the reader takes into account the full diversity of women, highlighting the effects of race, ethnicity, nationality, class, sexuality, and religion on women's experience. Theorizing feminisms is organized into four sections and includes fifty-four essays. The first section introduces several basic concepts commonly employed when thinking about sexism - oppression, social construction, essentialism, intersectionality, gender, race, and class - and also raises questions about the perspective and legitimacy of the theorist. The second section surveys three approaches that attempt to characterize in a general way the source of injustice toward women : humanist feminism ('the sameness approach'), gynocentric feminism ('the difference approach'), and dominance feminism. Offering an alternate perspective, the third section introduces two 'localizing' approaches, grounded in postmodernism and identity politics, respectively. Skeptical of theories that attempt to analyze social phenomena across history and culture, authors in this section challenge, rather than answer, the text's organizing questions. The final section explores the relationship of feminism theory to three liberatory projects - postcolonialism, neo-materialism, and queer theory - that do not characterize themselves as feminist, yet take gender as a significant category of analysis. Each section opens with an introduction and each essay is followed by helpful study questions. the majority of the essays are presented in their entirety. Theorizing feminisms underscores the strong connection between feminist theory and practice by including essays that illustrate important political inspirations or applications of each theoritical approach. It also presents versions of the same approach from various points in history, revealing feminist theory to be dynamic and evolving, rather than static. Ideal for interdisciplinary courses in feminist theory, this volume will also serve as an invaluable reference for current and future generations of theorists."
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; cours; discipline; essentialisme; intersectionnalité; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; thématiques; théorie féministe

Gender and Social Construction - Haslanger, Sally (Theorizing feminisms a reader, 2006)
Keywords: approches et analyses; cours; discipline; histoire et politique; phi4336; philosophie; philosophie politique; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques

Inside the gender Jihad: Women's reform in Islam - Wadud, Amina (Oneworld, 2006)
In her new book, Inside the Gender Jihad, Amina Wadud brings a wealth of experience from the trenches of the jihad to make a passionate argument for gender inclusiveness in the Muslim world. Knitting together scrupulous scholarship with lessons drawn from her own experiences as a woman, she explores the array of issues facing Muslim women today, including social status, education, sexuality, and leadership.
Keywords: cours; discipline; fem1000; femmes* musulmanes; genre; identités LGBTQIA2+; islam; philosophie; premier cycle; science des religions; sciences humaines; sexualité; thématiques